2003
DOI: 10.1073/pnas.2536696100
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila homolog of Down's syndrome critical region 1 gene regulates learning: Implications for mental retardation

Abstract: Mental retardation is the most common phenotypic abnormality seen in Down's syndrome (DS) patients, yet the underlying mechanism remains mysterious. DS critical region 1 (DSCR1), located on chromosome 21, is overexpressed in the brain of DS fetus and encodes an inhibitor of calcineurin, but its physiological significance is unknown. To study its functional importance and role in mental retardation in DS, we generated Drosophila mutants of nebula, an ortholog of human DSCR1. Here, we report that both nebula los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
119
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(126 citation statements)
references
References 35 publications
7
119
0
Order By: Relevance
“…In Ts16 mice, expression levels of DSCR1 isoforms, including alternative transcripts initiated from exon 1 and exon 4, are increased in the embryonic heart and brain relative to normal Ds16 embryos. Consistent with this observation, elevated expression of DSCR1 has been observed in the fetal brain of humans with Down syndrome (Fuentes et al, 2000;Chang et al, 2003). Although a mechanism by which increased DSCR1 expression may contribute to Down syndrome-related anomalies has not been identified, it is likely that altered regulation of calcineurin signaling would be involved.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In Ts16 mice, expression levels of DSCR1 isoforms, including alternative transcripts initiated from exon 1 and exon 4, are increased in the embryonic heart and brain relative to normal Ds16 embryos. Consistent with this observation, elevated expression of DSCR1 has been observed in the fetal brain of humans with Down syndrome (Fuentes et al, 2000;Chang et al, 2003). Although a mechanism by which increased DSCR1 expression may contribute to Down syndrome-related anomalies has not been identified, it is likely that altered regulation of calcineurin signaling would be involved.…”
Section: Discussionmentioning
confidence: 52%
“…During embryogenesis, DSCR1 is expressed in developing brain and craniofacial structures, thereby implicating DSCR1 in mental retardation, neurological disorders, and characteristic facies associated with Down syndrome (Casas et al, 2001;Reymond et al, 2002;Lange et al, 2004). Notably, elevated DSCR1 expression has been observed in the brain of individuals with Down syndrome and Alzheimer's disease (Fuentes et al, 2000;Ermak et al, 2001;Chang et al, 2003). In the embryonic heart, DSCR1 expression is consistent with a role in valvuloseptal development, and DSCR1(e4) expression in the valve endocardium is dependent on NFATc1, a transcription factor required for proper valve development (Casas et al, 2001;Lange et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2). We have previously shown that nebula can bind to and inhibit calcineurin activity and that flies overexpressing nla have perturbed calcineurin mediated signaling (13). Furthermore, dephosphorylation of synaptojanin by calcineurin stimulates the phosphoinositol 5Ј-phosphatase activity of synaptojanin (15).…”
Section: Regulation Of Synaptojanin Phosphoinositol 5 -Phophatase Actmentioning
confidence: 99%
“…Using Drosophila as a model system, we have previously shown that nebula (nla), the Drosophila ortholog of DS critical region 1 (DSCR1), also called regulator of calcineurin 1 (RCAN1) (11,12), binds to and inhibits the phosphatase activity of calcineurin, a protease involved in various biological pathways including learning and memory, and that altering the level of nebula leads to defective learning through calcineurin-mediated signaling (13). Among the many targets of calcineurin is synaptojanin (synj), a phosphatidylinositol phosphatase implicated in endocytosis (14).…”
mentioning
confidence: 99%
See 1 more Smart Citation